Overactive bladder symptom bother and health-related quality of life in patients with systemic lupus erythematosus and primary Sjögren syndrome. (January 2019) - Pereira e Silva, R; Romão, V C; Neves, M; Garcia, R; Oliveira, S; Brites, J; Ramos, F Oliveira; Canhão, H; Palma dos Reis, J; Pereira da Silva, J A; Lopes, T
Objective: The objective of this paper is to assess overactive bladder (OAB) symptom bother (SB) and health-related quality of life (HRQL) among patients with systemic lupus erythematosus (SLE) and primary Sjögren syndrome (pSS). Methods: We recruited adult SLE and pSS patients and two groups of age- and sex-matched controls. We applied the OAB questionnaire-short form (OABq-SF) to all participants to assess SB and HRQL and collected clinical information relevant for OAB. We compared the OABq-SF scores for SB and HRQL between patients and controls using univariate and multivariate linear regression analysis. Results: We recruited 95 rheumatic patients (68 SLE, 27 pSS) and 231 controls. Compared to controls SLE patients showed higher OABq-SF SB scores (22.6 ± 20.4 vs 14.7 ± 17.0, p = 0.004) and lower HRQL scores (89.8 ± 15.8 vs 93.8 ± 11.4, p = 0.044). On multivariate analysis SLE was significantly associated with a higher SB score (ß-coefficient 7.13, p = 0.008) and tended to be associated with worse HRQL values (ß-coefficient –3.53, p = 0.055). Patients with pSS had numerically higher mean SB scores (22.8 ± 22.5 vs 16.2 ± 18.0, respectively, p = 0.107) and lower HRQL scores (91.0 ± 10.7 vs 93.2 ± 11.6, respectively, p = 0.369), although these differences were not statistically significant. Diagnosis of pSS was not significantly associated with SB or HRQL scores on univariate or multivariate analysis. Conclusions: Patients with SLE have significantly worse OAB-SB and poorer HRQL compared to controls. A similar trend was seen for pSS patients, especially for SB. These findings suggest that clinically subtle OAB symptoms may be present in rheumatic patients for whom, later on, bladder pain syndrome may occur.